The "here and now" of youth: the meanings of smoking for sexual and gender minority youth - Tamar M. J. Antin; Geoffrey Hunt; Emile Sanders (BMC, 2018)
Abstract Background The mainstream tobacco field in the USA tends to situate youth as passive, particularly in terms of their susceptibility to industry manipulation and peer pressure. However, failing to acknowledge youths' agency overlooks important meanings youth ascribe to their tobacco use and how those meanings are shaped by the circumstances and structures of their everyday lives. Methods This article is based on analysis of 58 in-depth qualitative interviews conducted with sexual and gender minority youth living in the San Francisco Bay area in California. Topics covered in interviews focused on meanings of tobacco in the lives of youth. Interviews lasted approximately 2.5 h and were transcribed verbatim and linked with ATLAS.ti, a qualitative data analysis software. Following qualitative coding, narrative segments were sorted into piles of similarity identified according to principles of pattern-level analysis to interpret to what extent meanings of smoking for young people may operate as forms of resistance, survival, and defense. Results Analysis of our participants' narratives highlights how smoking is connected to what Bucholtz calls the "'here-and-now' of young people's experience, the social and cultural practices through which they shape their worlds" as active agents (Bucholtz, Annu Rev Anthropol31:525-52, 2003.). Specifically, narratives illustrate how smoking signifies "control" in a multitude of ways, including taking control over an oppressor, controlling the effects of exposure to traumatic or day-to-day stress, and exerting control over the physical body in terms of protecting oneself from violence or defending one's mental health. Conclusions These findings call into question the universal appropriateness of foundational elements that underlie tobacco control and prevention efforts directed at youth in the USA, specifically the focus on abstinence and future orientation. Implications of these findings for research, prevention, and policy are discussed, emphasizing the risk of furthering health inequities should we fail to acknowledge the "here and now" of youth.